MODERNIZING THE PRIVATE LAW. SOME KEY ISSUES IN THE RECENT DRAFT OF THE SPANISH COMMERCIAL CODE - Dan VELICU (Challenges of the Knowledge Society)
The last decades were dominated by the idea that an authentic process to modernize the private law means generally the unification of it by renouncing the distinction between civil and commercial law. A few European countries and some American states or provinces followed this path of the unification. However, beyond the will to change and improve the system one may reflect if this kind of modernization is actually really proper. Of course, there are lots of reasons for unification and reasons against it. Is there a possible and real alternative to this wave of unification? The draft of the Spanish commercial code could be a beginning point in order to settle this controversy. For the first time, the lawmakers are trying to replace the actual code with a new modernized one without renouncing the above mentioned distinction. Without claiming that we have entirely analyzed the topic, we propose a brief critical presentation of the major key issue of the draft.